Obesitas, body image, dan perasaan stres pada mahasiswa di Daerah Istimewa Yogyakarta - Dyah Ayu Kusuma Wardani; Emy Huriyati; Mustikaningtyas Mustikaningtyas; Janatin Hastuti (Jurnal Gizi Klinik Indonesia, 2015)
Background: Obesity can lead to various health problems including psychosocial problems. Obesity also relates to body image which may affect psychosocial health.Objective: To examine the relationship between obesity, body image, and perceived stress among college students in Yogyakarta Province.Method: This study is a cross-sectional design in 150 college students (75 boys and 75 girls) at Universitas Gadjah Mada and Universitas Technology Yogyakarta. Perceived stress was measured using 10 items of the Perceived Stress Scale (PSS-10), body image was evaluated using 16 items of the Body Shape Questionnaire (BSQ-16) and obesity was estimated using the percentage of body fat calculated from anthropometric measurements. Chi-square test, Spearman correlation analysis, and odds ratio were used to test the hypotheses.Results: There was significant correlation between obesity and body image in male (r= 0.32, p<0,01) and female students (r= 0.23, p<0,05). Obese male students were 7 times likely to have negative body image than non-obese male students. While no significant relationship was found between obesity and perceived stress,  non-obese students had almost two times likely to perceive stress. Similarly, body image was not significantly related to perceived stress in male and female students, however, it was likely that students with negative body image had about 1,5 times to feel stress than those with positive body image.Conclusion: Obesity was significantly associated with body image among male and female college students in Yogyakarta Province. However, no significant relationship was found between obesity and perceived stress as well as between body image and perceived stress among the students.